(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the role of theater pedagogy in higher education, specifically focusing on effective mechanisms for developing the professional competencies of students in philological fields. The outcomes of cultivating highly qualified teachers through theatrical techniques are highlighted. The article centers around experimental evidence, theoretical approaches, and practical recommendations.